(untitled) (American Journal of Islam and Society, 2009)
Immediately distinctive of Sachedina’s approach to biomedical ethics is his conception of the Shari`ah as an integrated legal-ethical tradition: The Qur’an provides jurists with moral underpinnings of religious duty, and the grounding texts are to be taken as an ethical standard of conduct. Legal rulings are to be extracted accordingly. In short, the Islamic juridical tradition (usul al-fiqh) presupposes ethics. Sachedina argues for an ethical foundation – a strong epistemological claim– and concerns himself with conceptual bases ofmoral reasoning rather than with juridically derived judgment per se. He elucidates deontologicalteleological principles that are “cross-culturally communicable” yet appreciative of “situational exigencies.” In contrast to the juridical objective of issuing legal opinions (fatwas), bioethical pluralism motivates Sachedina’s preference for recommended moral conduct (tawsiyah). He therefore moves away from the tendency of some scholars to conceive of bioethics merely as “applied Islamic jurisprudence.” The author’s epistemic and hermeneutic commitment commends his work, given the two facts that he identifies: (1) informed public debate on critical issues of biomedical ethics within Islam is lacking, relative to the degree of democratic governance, and (2) the epistemological and ontological bases of ethical inquiry remain underdeveloped in the Muslim seminarian curriculum. Consequently, there is a critical need to demonstrate to religious scholars that Islamic ethics have much in common with secular bioethics and thus that an opportunity for dialogue exists ...